2022
DOI: 10.3390/biomedicines10123172
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Cabozantinib in Patients with Advanced or Metastatic Renal Cell Carcinoma: A Multicenter Retrospective Cohort Study

Abstract: A multicenter retrospective study was conducted to evaluate the efficacy and safety of cabozantinib in patients with advanced or metastatic renal cell carcinoma (mRCC). We enrolled 53 patients with mRCC who received cabozantinib at eight institutions in Japan. The primary endpoint was overall survival (OS). The secondary endpoints were objective response rate (ORR), disease control rate (DCR), and progression-free survival (PFS). In addition, we analyzed prognostic factors in patients with mRCC treated with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The necessity for dose reduction, observed in 49% of our patients in this study, closely parallels findings from the METEOR and CABOSUN trials, where dose reductions were required in 62% and 46% of patients, respectively. In another real-world experience study conducted by Bodnar et al, the incidence of all AEs was reported at 100% [24], while a study conducted by Iinuma et al reported an incidence of 79% [25].…”
Section: Discussionmentioning
confidence: 92%
“…The necessity for dose reduction, observed in 49% of our patients in this study, closely parallels findings from the METEOR and CABOSUN trials, where dose reductions were required in 62% and 46% of patients, respectively. In another real-world experience study conducted by Bodnar et al, the incidence of all AEs was reported at 100% [24], while a study conducted by Iinuma et al reported an incidence of 79% [25].…”
Section: Discussionmentioning
confidence: 92%
“…The search yielded 222 papers, but only 51 of them were considered consistent with the topic of this paper were retrieved from PubMed. Then, we analyzed in detail and finally included information from 27 [ 15 , 18 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] publications that were considered useful for this manuscript, while the remaining references came from the personal knowledge of the authors [ 49 , 50 ]. In the end, we qualified 13 [ 15 , 26 , 27 , 28 , 29 , 31 , 33 , 34 , 35 , 42 , 44 , 51 , 52 ] works to formulate a table describing AEs; in the remaining 14 papers, information about AEs was insufficient.…”
Section: Methodsmentioning
confidence: 99%